Understanding the effects of surface modification on improving the high-voltage performance of Ni-rich cathode materials. (December 2018) - Liu, Siyang; Su, Junming; Zhang, Congcong; Chen, Xiang; Zhao, Jiayue; Huang, Tao; Wu, Jianhua; Yu, Aishui
Abstract: Ni-rich layered oxides are regarded as next-generation cathode materials for lithium-ion batteries with high energy density. However, these materials suffer capacity degradation and power fade at high cutoff voltages. Herein, a robust La, Zr nanocomposite oxide coating layer is successfully deposited on the LiNi0.6 Co0.2 Mn0.2 O2 surface using a wet-chemical method. The surface modified LiNi0.6 Co0.2 Mn0.2 O2 exhibits improved rate capability and superior cycling performance even at a high cutoff voltage of 4.5 V. Ex situ analyses uncover the capacity fading mechanisms of LiNi0.6 Co0.2 Mn0.2 O2 and the effects of the coating layer by a combination of X-ray diffraction, high-resolution transmission electron microscopy, and X-ray photoelectron spectroscopy. The results show that particle cracking, structural transformation, and interfacial side reactions are responsible for the inferior performance of pristine LiNi0.6 Co0.2 Mn0.2 O2 . Nevertheless, the coating layer not only retains structural integrity and suppresses irreversible surface phase transformation, but also alleviates accumulation of highly resistive species on the cathode surface. This investigation highlights the advantages of combining multiple techniques in investigating the effects of surface modification and could be extended to explore other coating materials. Graphical abstract: Highlights: A robust La, Zr nanocomposite oxide coating layer was obtained. LZNCM exhibits superior cycling stability under 3.0–4.5 V. Surface modification alleviates structural degradation. Surface modification suppresses electrolyte decomposition.